QUALITY PARAMETERS OF COW PEA SEEDS FOR DEVELOPMENT OF ORGANIZING STANDARD - L. V. Pavlov; A. P. Shtikhno; V. A. Sergeeva (Овощи России)
Based on data of varietal and sowing characteristics of caw pea seeds the organizing standard "Cow pea seeds. Varietal and sowing characteristics. Specifications" STO 45727225-40-2011 was developed.